Best Practice Leadership of The Principal in Covid-19 Prevention Primary School at SD Muhammadiyah Purbayan - Ulva Dian Citra Resmi; Enung Hasanah (RIRAI Publisher, 2020)
This research aims to determine how the principal carried out his duties in handling covid 19 transmissions in SD Muhammadiyah Purbayan. This study uses a descriptive qualitative method. The data collection techniques are carried out with interviews, observations, and literature studies. Interviews were conducted with teachers and employees of SD Muhammadiyah Purbayan Yogyakarta. Participants in this interview were selected through several criteria, including teachers and school employees directly involved by the school principal in covid-19 prevention. The validity of the data used is the triangulation technique. Data analysis techniques used are data reduction, data presentation, and conclusions. The results of this study show that; 1) the principal of SD Muhammadiyah Purbayan took steps to prevent transmission of the COVID 19 virus; 2) principals of schools which matters during the pandemic; 3) organizing school principals, assignments and to teachers and employees; 4) the principal together with teachers and employees from outside the school carry out activities which are planned, and 5) the principal of the hall which is the activity.